Detecting Disordered Eating Behaviors in Greek Youth with Type 1 Diabetes Mellitus by Using the Diabetes Eating Problem Survey—Revised (DEPS-R): Associations with Insulin Restriction, Glycemic Control, and Anthropometric Parameters - Anastasia Oikonomou; Athanasios Christoforidis; Eleni P. Kotanidou; Ioanna Giannopoulou; Eleni Paschalidou; Vasiliki Rengina Tsinopoulou; Georgia Sotiriou; Kyriaki Tsiroukidou; Assimina Galli-Tsinopoulou (Children, 2025)
Background/Objectives: This study assesses the prevalence of diabulimia in Greek children and adolescents with Type 1 Diabetes Mellitus (T1DM) by using the Diabetes Eating Problem Survey—Revised (DEPS-R) questionnaire and addresses a gap in the literature on eating disorders (EDs) and disordered eating behaviors (DEBs) in this population. The DEPS-R threshold score of ≥20, although originally established in international studies, has also been applied in Greek adult validation studies. However, it has not yet been formally validated in Greek youth. Methods: Participants aged 9–18 years, diagnosed with T1DM a minimum of one year before the start of the study, were recruited from three pediatric departments in Thessaloniki and were asked to complete the Greek version of the DEPS-R questionnaire. Appropriate statistical analysis was employed to investigate the association of the DEPS-R score with anthropometric, demographic, and glycemic variables derived from the clinical assessment and the patient’s medical records. Results: Girls had significantly higher DEPS-R scores compared with boys. Significant positive associations were observed between the DEPS-R score and both age (r = 0.212, p = 0.020) and Body Mass Index (BMI) (r = 0.419, p < 0.001). A significant association with Glycated Hemoglobin (HbA1c) (r = 0.182, p = 0.047) suggested that poorer glycemic control may be linked to disordered eating, although no significant associations were identified with physical activity or type of insulin therapy. Conclusions: Older age, higher Body Mass Index (BMI) and elevated Glycated Hemoglobin (HbA1c) levels are associated with increased risk of disordered eating in youth with T1DM, especially in girls. Therefore, the implementation of early screening and targeted interventions is imperative.